Melemahnya Kebebasan Pers Di Filipina - Viryawan, Muhammad Idham; Maritza, Shakila; Setyaningrum, Siti (Universitas Al Azhar Indonesia, 2022)
In the era of globalization that has happened so rapidly lately, journalists have given a new color to the world and broadcasting. This can be seen from how easy it is to get news from online news sites. Currently, it has also been regulated regarding the freedom of the press in obtaining and releasing news that will be consumed by the public, of course in accordance with the journalistic code of ethics. Not a few of the journalists who criticize the decisions of leaders in a country where it is done to build an upright democracy. However, it is unacceptable in the same way that the President of the Philippines did by closing and licensing the Rappler news agency who was innocent of defaming, spreading hoaxes, and embezzling tax funds. From this, the researcher wants to understand more deeply about the problem by revealing it in this scientific journal. The research method used is a qualitative method which is a literature study. And from this research, it can be concluded that the dictatorship of a leader from the Philippines has limited the human rights that can be done from closing the Rappler news agency because he does not want to damage his reputation as a leader, and it can be said that he always justifies all means in realizing the anti-criticism that exists within him. . In this case but asked by the journalist and owner of the Rappler News Agency, the Court will not accept it and win the president in the case.Keywords: Press Policy, Media, News Site, Closing